SIRT2 enhances 1-methyl-4-phenyl-1,2,3,6-tetrahydropyridine (MPTP)-induced nigrostriatal damage via apoptotic pathway - Liu, Lei; Arun, Anirudh; Ellis, Lakia; Peritore, Carina; Donmez, Gizem (Frontiers in Aging Neuroscience, 2014)
Sirtuins are NAD-dependent protein deacetylases that were shown to have protective effects against different age-related diseases. SIRT2 is a strong deacetylase that is highly expressed in brain. It has been associated with neurodegenerative diseases. MPTP (1-methyl-4-phenyl-1,2,3,6-tetrahydropyridine) is a dopaminergic neurotoxin that displays clinical features of Parkinson's Disease (PD). MPTP leads to the degeneration of nigrostriatal dopaminergic pathway after its systemic administration. Chronic administration of MPTP induces lesion via apoptosis. We show here that SIRT2 deacetylates Foxo3a, increases RNA and protein levels of Bim, and as a result enhances apoptosis in the MPTP model of PD. We also show that neurodegeneration induced by chronic MPTP regimen is prevented by genetic deletion of SIRT2 in mouse. Deletion of SIRT2 leads to the reduction of apoptosis due to an increase in acetylation of Foxo3a and a decrease in Bim levels. We demonstrate that SIRT2 deacetylates Foxo3a, activates Bim, and induces apoptosis only in MPP+-treated cells. Therefore, designing SIRT2 inhibitors might be helpful in developing effective treatments for PD.